Integrating logarithms

Calculus Level 4

0 ln ( 1 + x 2 ) ( 1 + x 2 ) d x \large \int_0^\infty \dfrac{\ln(1+x^2)}{(1+x^2)}\; dx

If the value of the above integral can be written as A π ln ( B ) A\pi\ln(B) for positive integers A A and B B , then enter the value of 10 A + 11 B 10A+11B .


The answer is 32.

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

2 solutions

Let, I = 0 ln ( 1 + x 2 ) 1 + x 2 d x Now, let x = tan θ , d x = sec 2 θ d θ I = 0 π 2 ln ( 1 + tan 2 θ ) 1 + tan 2 θ sec 2 θ d θ = 0 π 2 ln ( 1 + tan 2 θ ) d θ = 2 0 π 2 ln ( cos θ ) d θ = 2 0 π 2 ln ( sin θ ) d θ a b f ( x ) d x = a b f ( a + b x ) d x 2 I = 2 0 π 2 ln ( cos θ ) d θ + 2 0 π 2 ln ( sin θ ) d θ = 2 0 π 2 ln ( sin 2 θ 2 ) d θ = 2 0 π 2 ln ( sin 2 θ ) d θ + 2 0 π 2 ln 2 d θ = 2 0 π 2 ln ( sin 2 θ ) d θ + π ln 2 Let, t = 2 θ , d t = 2 d θ 2 I = 0 π ln ( sin t ) d t + π ln 2 = 2 0 π 2 ln ( sin t ) d t + π ln 2 sin ( π t ) = sin t , thus 0 π ln ( sin t ) d t = 2 0 π 2 ln ( sin t ) d t 2 I = I + π ln 2 I = π ln 2 10 A + 11 B = 10 ( 1 ) + 11 ( 2 ) = 32 \begin{aligned}\text{Let, } I&=\int_{0}^{\infty} \dfrac{\ln(1+x^2)}{1+x^2} dx\\\\ \text{Now, let }x&=\tan\theta,dx=\sec^{2}\theta \cdot d\theta\\ I&=\int_{0}^{\tfrac{\pi}{2}} \dfrac{\ln(1+\tan^{2}\theta)}{1+\tan^{2}\theta}\hspace{3mm}\sec^{2}\theta\cdot d\theta\\ &=\int_{0}^{\tfrac{\pi}{2}} \ln(1+\tan^{2}\theta)\hspace{2mm}d\theta\\ &=-2\int_{0}^{\tfrac{\pi}{2}} \ln(\cos\theta)\hspace{2mm}d\theta\\ &=-2\int_{0}^{\tfrac{\pi}{2}} \ln(\sin\theta)\hspace{2mm}d\theta\hspace{7mm}\color{#3D99F6}\small\int_{a}^{b}f(x)\hspace{2mm}dx=\int_{a}^{b}f(a+b-x)\hspace{2mm}dx\\\\ \implies 2I&=-2\int_{0}^{\tfrac{\pi}{2}} \ln(\cos\theta)\hspace{2mm}d\theta+-2\int_{0}^{\tfrac{\pi}{2}} \ln(\sin\theta)\hspace{2mm}d\theta\\ &=-2\int_{0}^{\tfrac{\pi}{2}}\ln\left(\dfrac{\sin2\theta}{2}\right)\hspace{2mm}d\theta\\ &=-2\int_{0}^{\tfrac{\pi}{2}}\ln(\sin2\theta)\hspace{2mm}d\theta+2\int_{0}^{\tfrac{\pi}{2}}\ln2\hspace{2mm}d\theta\\ &=-2\int_{0}^{\tfrac{\pi}{2}}\ln(\sin2\theta)\hspace{2mm}d\theta+\pi\ln2\\\\ \text{Let, t}&=2\theta,dt=2\cdot d\theta\\ \implies 2I&=-\int_{0}^{\pi}\ln(\sin t)\hspace{2mm}dt+\pi\ln2\\ &=-2\int_{0}^{\tfrac{\pi}{2}}\ln(\sin t)\hspace{2mm}dt+\pi\ln2\hspace{7mm}\color{#3D99F6}\small\sin(\pi-t)=\sin t,\text{ thus }\int_{0}^{\pi}\ln(\sin t)\hspace{2mm}dt=2\int_{0}^{\tfrac{\pi}{2}}\ln(\sin t)\hspace{2mm}dt\\\\ \implies 2I&=I+\pi\ln2\\ I&=\pi\ln2\\ 10A+11B&=10\cdot (1)+11\cdot (2)=\color{#EC7300}\boxed{\color{#333333}32}\end{aligned}

Denote our integral by F ( n ) = 0 ln ( 1 + x n ) 1 + x n d x \displaystyle F(n)=\int_0^\infty \dfrac{\ln(1+x^n)}{1+x^n}\; dx for n : { n R n > 1 } n\;:-\;\{n\in\mathbb{R}|n>1\} .

F ( n ) = 0 ln ( 1 + x n ) 1 + x n d x = 1 n 1 ln x x ( x 1 ) 1 / n 1 d x Set ( 1 + x n ) x = 1 n 0 1 t 1 n ( 1 t ) 1 n 1 ln t d t Set x 1 x = 1 n a ( 0 1 t a ( 1 t ) b d t ) a = 1 n , b = 1 n 1 = 1 n a [ β ( a , b ) ] a = 1 1 n , b = 1 n = 1 n β ( 1 1 n , 1 n ) [ ψ ( 1 1 n ) + γ ] = 1 n × Γ ( 1 1 n ) Γ ( 1 n ) × ( ψ ( 1 1 n ) + γ ) = π sin ( π n ) n ( ψ ( 1 1 n ) + γ ) Since Γ ( x ) Γ ( 1 x ) = π sin ( π x ) \displaystyle \begin{aligned} F(n)&= \int_0^\infty \dfrac{\ln(1+x^n)}{1+x^n}\; dx \\ &= \dfrac{1}{n}\int_1^\infty \dfrac{\ln x}{x} (x-1)^{1/n-1}\; dx \quad\color{#3D99F6}{\text{Set } (1+x^n)\to\; x} \\ &= \dfrac{-1}{n} \int_0^1 t^{\dfrac{-1}{n}} (1-t)^{\dfrac{1}{n}-1}\ln t\; dt\quad\color{#3D99F6}{\text{Set }x\to\dfrac{1}{x}} \\ &= \dfrac{-1}{n}\dfrac{\partial}{\partial a}\left(\int_0^1 t^a (1-t)^b\;dt\right)_{a=\frac{-1}{n} , b=\frac{1}{n}-1} \\ &= \dfrac{-1}{n}\dfrac{\partial}{\partial a}\left[\beta(a,b)\right]_{a=1-\frac{1}{n},b=\frac{1}{n}} \\ &= -\dfrac{1}{n}\beta\left(1-\dfrac{1}{n},\dfrac{1}{n}\right)\left[\psi\left(1-\dfrac{1}{n}\right)+\gamma\right] \\ &= \dfrac{-1}{n}\times \dfrac{\Gamma\left(1-\dfrac{1}{n}\right)\Gamma\left(\dfrac{1}{n}\right)}\times \left(\psi\left(1-\dfrac{1}{n}\right)+\gamma\right) \\ &= \dfrac{-\pi}{\sin\left(\dfrac{\pi}{n}\right)n}\left(\psi\left(1-\dfrac{1}{n}\right)+\gamma\right) \quad\text{Since } \Gamma(x)\Gamma(1-x)=\dfrac{\pi}{\sin(\pi x)}\end{aligned}

Put n = 2 n=2 to get the answer using ψ ( 1 2 ) = 2 ln 2 γ \psi\left(\dfrac{1}{2}\right)=-2\ln 2-\gamma as π ln 2 \boxed{\pi\ln 2} and the answer is 32 32

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...